FARMERS INSTITUTIONAL STRENGTHENING WITH AGRIBUSINESS MODEL OF PADDY RICE BREEDING THROUGH KKN-PPM PROGRAM OF LAKIDENDE UNIVERSITY - Rayuddin Rayuddin (Universitas Tribhuwana Tunggadewi, 2020)
A study of agribusiness model of breeding of rice paddy seeds throught community development program (KKN)- community empowerment learning (PPM) of Lakidende Univercity aimed to increase institutional capacity of farmers in producing rice seed products with the use of high quality rice varieties. So far, the access to high quality rice seedlings in the farmer group business unit of rice seed breeders is still low and limited procurement in every rice planting season. Mean while, the need of rice seed in Konawe Recency averagely 415.000 tons of planting season with the fulfillment of seed supply from breeder farmer group only about 87.830 tons of planting season (21,16 %). In the study method with KKN-PPM spproach, the students and society conducted a study of the implementation of agribusiness field schools (SL-A) in farmer group of rice seed breeders in Ambuulanu village, Pondidaha sub-district, Konawe Regency. The study was implemented for 33 working days (July- Agusts 2016). The result of study of farmer institutional strengthening on the farmer group of paddy rice breeder farming unit showed that the institutional strengthening system of farmer group of paddy rice breeder in rural communities with the application of model field school agribusiness in the implementation of KKN-PPM program, is potentially able to meet the supply of high quality seeds with the average production as mush as 456.5 tons of rice seed ready to spread in each wet season rice fiel, and effective in the learning model of rural community empowerment with Univercity in Konawe district area.